2016
DOI: 10.12957/reuerj.2016.11637
|View full text |Cite
|
Sign up to set email alerts
|

Enfermeiros gerentes de um hospital de ensino: formação profssional, responsabilidades e desafos [Nurse managers at a teaching hospital: training, responsibilites and challenges]

Abstract: Objetivo: conhecer o perfil do enfermeiro gerente hospitalar conforme os aspectos sociodemográficos e de formação profissional, identificando os desafios enfrentados. Método: estudo descritivo, quantiqualitativo, realizado em junho de 2014 em um hospital público de ensino do interior paulista, no qual participaram 15 enfermeiros gerentes. Foram utilizadas entrevistas semiestruturadas com análise temática dos dados, a qual gerou as categorias: Capacitação para as atribuições de gerente de enfermagem; Tornar-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
8
Order By: Relevance
“…Other authors (25)(26) argue that it is necessary to invest in improving evaluation and monitoring of work in organizations, with the objective of achieving excellence in care. Therefore, it is necessary to focus on the qualification of professionals and the analysis of the social, political, economic and health context.…”
Section: Descriptoresmentioning
confidence: 99%
“…Other authors (25)(26) argue that it is necessary to invest in improving evaluation and monitoring of work in organizations, with the objective of achieving excellence in care. Therefore, it is necessary to focus on the qualification of professionals and the analysis of the social, political, economic and health context.…”
Section: Descriptoresmentioning
confidence: 99%
“…professionals in this sample, it was found that this is a prevalent scenario in studies conducted in other the majority was female (89%) 8,[11][12][13][14] . In a study that outlined the profile of the stomatherapist graduated from the University of Taubaté, it was identified the predominance of female specialists in stomatherapy (29/96.6%) 15 .…”
Section: G I Ve N T H E M a J O R I T Y O F F E M A L E S A M On G T H Ementioning
confidence: 57%
“…In their work environment, nursing managers are faced with several realities and challenges, without, however, having a defined managerial model. Human, financial and physical resources are a few of the components that generate problems to be faced, and the immediate resolution does not always generate efficient work, being necessary to look beyond immediacy, thus, knowledge on management becomes a potential transformative instrument of practice (13) .…”
Section: Discussionmentioning
confidence: 99%